TRANLITERASI DESKRIPSI BIBLIOGRAFI KOLEKSI BAHASA ARAB - Bustanul Syukri (UIN Imam Bonjol Padang, 2019)
Abstract: Transliteration of bibliographic descriptions in Arabic collections is one of the activities that must be done by catalogers to process library materials. Because the space and size of standardized catalog cards is very limited for cataloging Arabic collections. Along with that, starting in 1987 the handbook of Arabic-Latin transliteration as a result of the decision of the Minister of Religion and the Minister of Education and Culture of the Republic of Indonesia has greatly helped catalogers to transliterate bibliographic descriptions in Arabic collections. However, if the word loger has no knowledge in the Arabic language field, it will certainly lead to difficulties in carrying out the task of librarians processing collections in Arabic.Keyword: Transliteration, Collection in ArabicAbstrak: Transliterasi deskripsi bibliografi koleksi berbahasa arab adalah salah kegiatan yang harus dilakukan oleh kataloger untuk mengolah bahan pustaka. Karena ruang dan ukuran kartu katalog yang sudah standard/dibakukan sangat terbatas untuk katalogisasi koleksi berbahasa arab. Seiring dengan itu, mulai tahun 1987 buku panduan transliterasi arab-latin hasil keputusan Menteri Agama dan Menteri Pendidikan dan Kebudayaan RI sudah sangat membantu kataloger untuk melakukan transliterasi deskripsi bibliografi koleksi berbahasa arab. Namun bilamana kataloger tidak memiliki pengetahuan dalam bidang bahasa arab, tentu akan mengalami kesulitan untuk melakukan tugas kepustakawanan mengolah koleksi-koleksi yang berbahasa arabKata Kunci: Transliterasi, Koleksi Berbahasa Arab